Correlation Between Family Cohesion and Recurrence in Schizophrenics at the dr. Soetomo Hospital Psychiatric Clinic - Texaga, Derryl Rasad; Khairina; Purwo Sri Rejeki (Faculty of Medicine, Universitas Airlangga, 2022)
ABSTRACTBackground; Schizophrenia recurrence is caused by many factors, one of which is family factors. Family is very important for people with schizophrenia, where one of the roles and functions of the family is to provide an affective function to meet the psychosocial needs of family members in providing affection. Objective; This study was conducted with the aim of knowing the correlation between family cohesion and recurrence in schizophrenic patients at the Dr. Soetomo Hospital Psychiatric clinic. Methods; This research method using observational-analytic design with cross-sectional approach with a sample of schizophrenic patients at the Psychiatry Clinic of dr. Soetomo Hospital Surabaya in June-August 2020 which met the inclusion criteria. The variables studied were family cohesion and recurrence of schizophrenia. Samples were taken using total sampling with a sample size of 40 research subjects. Sampling was conducted at the dr. Soetomo Hospital Psychiatry Clinic. Data analysis was performed using the Spearman correlation analysis technique. Results; The results of the Spearman correlation analysis showed a correlation coefficient of -0.291 with a significance value of 0.69 (p> 0.05). Conclusion; It can be concluded that the relationship between the two variables is not unidirectional and there is no significant relationship between family cohesion and recurrence in schizophrenics at the dr. Soetomo Hospital Psychiatry Clinic. Keywords: Family Cohesion, Schizophrenia Recurrence, Schizophrenic Patients